From Discounts to Impulse Buys: How Shopping Lifestyles and Positive Emotions Influence Consumer Behavior - Zaki, Muhammad; Simon, Zainal Zawir (SAN Scientific, 2025)
This study investigates how discounts and shopping lifestyle influence impulsive purchases among Shopee users in Central Jakarta, with positive emotions as an intervening variable and viewed from an Islamic perspective. A total of 144 respondents were selected using purposive sampling. Data was collected through a questionnaire-based survey and analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) and SPSS. The findings revealed that discounts do not directly affect impulsive purchases but do have a significant positive impact on positive emotions. In contrast, shopping lifestyle significantly influences both impulsive purchases and positive emotions. Furthermore, positive emotions significantly impact impulsive buying behavior and mediate the relationship between discounts and impulsive purchases, as well as between shopping lifestyle and impulsive purchases. From a managerial standpoint, businesses can strategically offer discounts during holidays or weekends to trigger positive emotions and boost sales. Enhancing the overall shopping experience through appealing app interfaces, engaging content, and responsive customer service can foster positive emotions that drive impulsive purchases. From an Islamic perspective, ethical marketing practices that avoid deception and encourage moderation in consumption should be upheld, ensuring that promotional efforts align with Islamic principles of fairness, honesty, and responsible consumer behavior.